Urological injuries associated with pelvic fractures: A case report of a detached bone segment inside the bladder. (2016) - Alfayez, Saud M.; Allimmia, Khalid; Alshammri, Ahmad; Serro, Firas; Almogbel, Rakan; Bin Dous, Abdullah; Almannie, Raed; Palencia, Jesús
Highlights: A 45-year-old pedestrian male was hit by a car. Gross hematuria was evident upon inserting Foley's catheter. CT revealed multiple stable pelvic fractures. CT cystogram showed intraperitoneal and extraperitoneal extravasation of contrast. A detached pubic bone fragment was found inside the urinary bladder. Abstract: Introduction: Urological injuries in pelvic fractures are noticed in 6–15% of the cases. The bladder, due to its anatomical position, is prone to rupture in pelvic fractures. The majority of urinary bladder injuries are either extraperitoneal or intraperitoneal. Nonetheless, both types can occur simultaneously in 6% of the cases. Presentation of the case: A 45-year-old male was brought to our emergency department after being struck by an automobile. In the absence of signs of urethral injury, a Foley's catheter was inserted revealing gross hematuria. The radiological assessment showed bilateral non-displacement sacral wing fractures, bilateral non-displacement anterior column fractures and bilateral comminuted superior and inferior pubic rami fractures, with a detached pubic bone fragment displaced posteriorly. A CT cystogram was performed showing intraperitoneal and extraperitoneal extravasation of contrast. The patient was taken to surgery. A sharp-edged bony fragment was discovered inside the bladder. A two-layer closure of the bladder was performed. Discussion: Pelvic fractures with concomitant lower urinary tract injuries are associated with high morbidity and mortality. The signs indicative of bladder rupture include a more than one centimeter diastasis of the symphysis pubis and a displaced fracture of more than one centimeter involving the obturator ring. However, the signs may not be present as in our case. Conclusion: This unusual case illustrates the potential risk of bladder injury following stable pelvic fractures through a detached bone segment. It also emphasizes on having a high index of suspicion. The teamwork and multidisciplinary approach are essential for an optimal outcome.